A Review Paper on Influence of Process Parameters in a Cold Chamber under High Pressure Die Casting - Satendra Kumar Verma; Mr. Dinesh Dubey (International Journal of Scientific Research in Civil Engineering, 2025)
Die castings are among the most frequently produced mass-market goods in the metal working sector for complicated forms and Aluminium alloy that is lightweight. The needs of getting the light weight components with the same or improved mechanical, metallurgical properties, the industry is switching on these types of alloys. The present study is aimed at investigating the impact of various process parameters of cold chamber high pressure die casting machine on the cast product. Moreover the process parameters are further optimized with the aim to get optimum product quality.
Keywords: Die castings; Aluminium alloy; Process parameters; Cast product; Product quality